Implementing the “Show-and-Tell” Method to Improve Students’ Speaking Skills - Salsabila, Hasna; Ahsanu, Muhamad; Kariadi, Mustasyfa Thabib; Riyadi, Slamet (LPPM Universitas Pekalongan, 2023)
This study aimed to find out the implementation of the